2022
DOI: 10.3389/fonc.2022.836117
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms in Inflammation Genes With the Prognosis of Advanced Non-Small Cell Lung Cancer Patients Receiving Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors

Abstract: BackgroundInflammation is not only involved in the development and progression of cancer but also affects the response to therapy. The aim of this study was to investigate the association of single nucleotide polymorphisms (SNPs) in inflammation genes with the prognosis of advanced non-small cell lung cancer (NSCLC) patients treated with epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs).MethodsForty-seven SNPs were genotyped in 318 advanced NSCLC patients receiving EGFR-TKIs. Of 318 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Dai and Fu 62 constructed a prognostic model based on a panel of six necrosis‐related genes, including TNFRSF1A, to assess the prognosis of patients with LUAD. Zhang et al 63 demonstrated that high expression of TNFRSF1A was also associated with a poorer prognosis in patients with LUAD. Overexpression of RAC1 has been reported to be associated with EMT, which is able to promote tumor metastasis and progression in NSCLC through EMT 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Dai and Fu 62 constructed a prognostic model based on a panel of six necrosis‐related genes, including TNFRSF1A, to assess the prognosis of patients with LUAD. Zhang et al 63 demonstrated that high expression of TNFRSF1A was also associated with a poorer prognosis in patients with LUAD. Overexpression of RAC1 has been reported to be associated with EMT, which is able to promote tumor metastasis and progression in NSCLC through EMT 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the rs4819554 variant was significantly associated with worse progression-free survival and overall survival in patients with non-small cell lung cancer (NSCLC) [ 99 ]. Similarly, homozygosity for the AA genotype was linked to more significant deterioration of renal function [ 98 ] and increased primary graft dysfunction after lung transplantation [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that overexpression of YWHAE strengthens the invasiveness of breast cancer cells 22 , but no other studies have probed the impact of YWHAE on the outcome of LUAD. Preexisting research has shown that the overexpression of TNFRSF1A, ADM, ITGB1, PRMT1, and AREG is associated with an unfavorable prognosis in patients 23 - 27 . The model based on the above eight EIRGs showed that it has good predictive value, and similar results were obtained in the GEO external cohort.…”
Section: Discussionmentioning
confidence: 99%